PENILAIAN KINERJA KOPERASI JASA KEUANGAN SYARIAH - Andriani Andriani; Rizky Kurniawan Pambudi (Jurnal Ekonomi Integra, 2022)
The focus of this research is how to compare the performance analysis of BMT Lantasir and KSPPS BMW Ar Rahmah East Java based on Permenkop No. 07/PER/DEP.6/IV/2016. This research approach is qualitative. The type of this research is a case study in this study the presence of the researcher acts as an instrument as well as data collector. Each cooperative is required to have maximum performance based on Permenkop number 16/Per/M.KUKM/- IX/2015 it is explained that as a sharia financial institution, sharia savings and loan businesses and sharia financing by cooperatives carry out intermedia functions that have their own characteristics, forms and systems must be regulated, monitored and assessed for health. Health assessment needs to be carried out every year to determine the level of health in terms of finance, management aspects and compliance with sharia principles.Based on this research, it can be concluded that the health analysis of Sharia Savings and Loans and Financing Cooperatives (KSPPS) based on Permenkop No. 07/PER/DEP.6/IV/2016 at BMT Lantasir and KSPPS BMW Ar Rahmah Jatim, both of them received the title; Healthy enough. With a difference in score of 7.15% with the score obtained by each institution, BMT Lantasir gets a score of 68.80 (Max. 100). And KSPPS BMW Ar Rahmah East Java got a score of 75.95 (Max.100).